PENGARUH KUALITAS PELAYANAN PEGAWAI TERHADAP LOYALITAS PELANGGAN PDAM KABUPATEN BANJARNEGARA - Arfiani, Fauziah; Supriliyani, Ni Wayan; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER; Vol 1 No 2 (2019), 2019)
ABSTRACT   Primary data in this study were obtained through questionnaires as many as 100 samples of customers of PDAM Banjarnegara, The results of the analysis of the findings of this study indicate that the partial effect of service quality (X) on customer loyalty (Y) in PDAM Banjarnegara Regency is positive. This is based on the results of linear regression analysis which obtained a positive regression coefficient of 0.460. The results of tcount = 15.859 and ttable = 1.98397 which means tcount> t table with a significance value of 0.000 <0.05. So, it can be concluded that there is a partial effect of service quality on customer loyalty in PDAM Banjarnegara Regency is significantly positive. The influence of determinant of service quality on customer loyalty in PDAM Banjarnegara Regency is 72%. customer loyalty in PDAM Kabupaten Banjarnegara is influenced by the quality of services available. Keywords: Service Quality, Customer Loyalty, PDAM